A blueprint for synthetic control methodology: a causal inference tool for evaluating natural experiments in population health. (23rd November 2022) - Barr, Ben; Zhang, Xingna; Green, Mark; Buchan, Iain
Abstract : Interventions in emergencies such as the covid-19 pandemic may need rapid supporting evidence. Randomised trials in these situations are often impractical to design or deliver. One technique for estimating the causal effect of an intervention using observational data is the synthetic control method. This article outlines the method and its assumptions, best practice interpretation, and application.